Legal features of competitive obligations under the civil legislation of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2021)
The article analyzes specific aspects of civil regulation of the competitive obligation. The high importance and lack of practical development of the above problem determine scientific work’s undoubted novelty. Further attention to the civil principle of competitive responsibility is needed to better and rationally address civil law’s current concerns. Competitive commitments represent another type of unilateral commitment. They clearly show the features of obligations, which in the private law of foreign countries are called quasi-contract. The content of these obligations may cover those actions of the contestants on the competitive task that is usually performed by debtors under some civil law contracts – contracts, orders, commissions, and others. It is not ruled out for the contestants to commit legal acts, creating science, literature, and art. In the first case, it is not a question of the actual commission of legally significant actions by the contestants in favor of the subject who announced the contest, but about their readiness for legal obliging themselves in exchange for compliance with the person of their condition who disclosed the conflict. Public competitions are once again widespread in the civil circulation. Simultaneously, the comparison of the practice of holding available games with the provisions of civil law shows that public competitions are, in many cases, held in contravening the law. One of the many reasons for this is the imperfection of legal regulation and the lack of good ideas about the Civil Code of Kazakhstan requirements for public competition and their complete or partial disregard.Key words: competition, obligation, regulation, public customer, organizer, specifics of competitive responsibilities, types of games.